Extracellular Galectin-3 in Tumor Progression and Metastasis - Fortuna-Costa, Anneliese; Gomes, Angélica M.; Kozlowski, Eliene O.; Stelling, Mariana P.; Pavão, Mauro S. G. (Frontiers in Oncology, 2014)
Galectin-3, the only chimera galectin found in vertebrates, is one of the best-studied galectins. It is expressed in several cell types and is involved in a broad range of physiological and pathological processes, such as cell adhesion, cell activation and chemoattraction, cell cycle, apoptosis, and cell growth and differentiation. However, this molecule raises special interest due to its role in regulating cancer cell activities. Galectin-3 has high affinity for β-1,6-N-acetylglucosamine branched glycans, which are formed by the action of the β1,6-N-acetylglucosaminyltransferase V (Mgat5). Mgat5-related changes in protein/lipid glycosylation on cell surface lead to alterations in the clustering of membrane proteins through lattice formation, resulting in functional advantages for tumor cells. Galectin-3 presence enhances migration and/or invasion of many tumors. Galectin-3-dependent clustering of integrins promotes ligand-induced integrin activation, leading to cell motility. Galectin-3 binding to mucin-1 increases transendothelial invasion, decreasing metastasis-free survival in an experimental metastasis model. Galectin-3 also affects endothelial cell behavior by regulating capillary tube formation. This lectin is found in the tumor stroma, suggesting a role for microenvironmental galectin-3 in tumor progression. Galectin-3 also seems to be involved in the recruitment of tumor-associated macrophages, possibly contributing to angiogenesis and tumor growth. This lectin can be a relevant factor in turning bone marrow in a sanctuary for leukemia cells, favoring resistance to therapy. Finally, galectin-3 seems to play a relevant role in orchestrating distinct cell events in tumor microenvironment and for this reason, it can be considered a target in tumor therapies. In conclusion, this review aims to describe the processes of tumor progression and metastasis involving extracellular galectin-3 and its expression and regulation.